The Interplay between Surface Plasmon Resonance and Switching Properties in Gold@Spin Crossover Nanocomposites. (27th February 2020) - Palluel, Marlène; Tran, Ngoc Minh; Daro, Nathalie; Buffière, Sonia; Mornet, Stéphane; Freysz, Eric; Chastanet, Guillaume
Abstract: Rod‐like gold nanoparticles are directly embedded in a 1D‐polymeric spin crossover (SCO) material leading to singular Au@SCO nanohybrid architectures. The resulting architectures are designed to promote a synergetic effect between ultrafast spin‐state photoswitching and photothermal properties of plasmonic nanoparticles. This synergy is evidenced by the strong modulation of the surface plasmon resonance of the gold nanorods through the spin‐state switching of the SCO component and also the strong enhancement of the photoswitching efficiency compared to pure SCO particles. This remarkable synergy results from the large modulation of the dielectric properties of the SCO polymer upon its thermal switching and the enhancement of the heating of these hybrid nanostructures upon excitation of the surface plasmon resonance of the gold nanorods. Abstract : The synthesis of unprecedented gold@spin crossover (Au@SCO) nanocomposites is reported. They exhibit a strong interplay between surface plasmon resonance (SPR) and spin state switching. The spin state change induces a 35 nm modulation of the longitudinal SPR of the gold core. The latter acts as a local nanoheater to enhance the photothermal effect and the subsequent photoinduced SCO.